1998
DOI: 10.1128/jcm.36.12.3480-3487.1998
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Verocytotoxin-ProducingEscherichia coliO157 on Dutch Dairy Farms

Abstract: During the period from September 1996 through November 1996, 10 Dutch dairy farms were visited to collect fecal samples from all cattle present. The samples were examined for the presence of verocytotoxin (VT)-producing Escherichia coli (VTEC) of serogroup O157 (O157 VTEC) by immunomagnetic separation following selective enrichment. Cattle on 7 of the 10 dairy farms tested positive for O157 VTEC, with the proportion of cattle infected varying from 0.8 to 22.4%. On the seven farms positive for O157 VTEC, the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(75 citation statements)
references
References 38 publications
9
64
2
Order By: Relevance
“…The low prevalence of STEC O157 detected in milking cows (0AE2%) and calves (0AE8%) agrees with results obtained by LeJeune et al (2006) who found 0AE6% of O157 in dairy cows from Ohio (USA). A previous study carried out in a feedlot from Argentina shows higher percentages of STEC O157 (6AE8%) when the animals were serially sampled (Padola et al 2004) and these results were similar to those found in dairy cattle from other countries (Chapman et al 1993;Heuvelink et al 1998;Jackson et al 1998;Vold et al 1998;Synge and Paiba 2000;Nielsen et al 2002;Fitzgerald et al 2003;Vicente et al 2005). These data indicate that STEC O157 is an uncommon serogroup for bovine in Argentina, although it has been isolated from cattle and human faeces by other authors in this country (Orskov et al 1987;Rivas et al 1996;Padola et al 2004).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The low prevalence of STEC O157 detected in milking cows (0AE2%) and calves (0AE8%) agrees with results obtained by LeJeune et al (2006) who found 0AE6% of O157 in dairy cows from Ohio (USA). A previous study carried out in a feedlot from Argentina shows higher percentages of STEC O157 (6AE8%) when the animals were serially sampled (Padola et al 2004) and these results were similar to those found in dairy cattle from other countries (Chapman et al 1993;Heuvelink et al 1998;Jackson et al 1998;Vold et al 1998;Synge and Paiba 2000;Nielsen et al 2002;Fitzgerald et al 2003;Vicente et al 2005). These data indicate that STEC O157 is an uncommon serogroup for bovine in Argentina, although it has been isolated from cattle and human faeces by other authors in this country (Orskov et al 1987;Rivas et al 1996;Padola et al 2004).…”
Section: Discussionsupporting
confidence: 81%
“…In France, the prevalence obtained was similar (Fremaux et al 2006). These values were higher than those found in some countries such as the Netherlands (8AE8-22AE4%) (Heuvelink et al 1998), Australia (16AE7%) (Cobbold and Desmarchelier 2000) and the USA (8%) (Wells et al 1991). However, there are countries with higher prevalence such as Switzerland (44AE3%) (Busato et al 1999), Canada (62AE1%) (Jackson et al 1998) and Brazil (52-82%) (Leomil et al 2003;Moreira et al 2003;Vicente et al 2005).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Using a sensitive ELISA method, Zhao et al (1995) detected STEC O157:H7 in 22% of investigated control herds, from which E. coli O157:H7 had not been isolated previously. In a Dutch study, using immunomagnetic separation technique, STEC O157 occurred in seven out of 10 dairy farms (Heuvelink et al 1998). Kudva et al (1997) isolated and characterized E. coli O157:H7 and non-O157 STEC strains from sheep.…”
Section: Discussionmentioning
confidence: 99%